Penyimpanan Mata Uang Asing Palsu dan Penggunaan Uang Hasil Transfer Dana yang Bukan Miliknya: Suatu Tinjuan dari KUHP dan Undang-undang No. 3 Tahun 2011 tentang Transfer Dana - Sutantyo, Priscillia Tiffany (Al-Jinayah : Jurnal Hukum Pidana Islam, 2020)
Abstract: The paper aims to analyze whether the conducts of S, who has the counterfeit foreign currency with the intention of circulating the money and the use of the transferred funds that do not belong to him are under the Criminal Code and the Funds Transfer Law. The results of the study showed that S infringed the Article 245 of the Criminal Code which proved that S kept counterfeit foreign currency with the intent of distributing the money through his actions of keeping 10 (ten) pieces of 100 (one hundred) United States dollars which he obtained from A, a friend of S at Bima's Terminal. S also had violated Article 85 of the Funds Transfer Law through his act of utilizing the transferred money that did not belong to him. S knew that the money transferred to his account was not from the platinum metal buyer, based on a telephone's statement between the platinum metal buyer and S, who then took the money from his account and used the money. Therefore, S should be liable for his criminal actions.